2019
DOI: 10.1016/j.gloenvcha.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Human health as a motivator for climate change mitigation: results from four European high-income countries

Abstract: Invoking health benefits to promote climate-friendly household behavior has three unique advantages: (i) health co-benefits accrue directly to the acting individual, they are "private goods" rather than public ones; (ii) the evidence base and magnitude of health co-benefits is well-established; and (iii) the idea of a healthy lifestyle is well-engrained in public discourse, much more so than that of climate-friendly lifestyle. In previous research assessing the influence of information on health effects on peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 31 publications
1
46
0
3
Order By: Relevance
“…Furthermore, this study contributes to consolidate the use of the theory of awe to explain green consumption behavior, showing new results that help to clarify the mediational role of environmental concern and risk aversion to predicting green consumption behavior. For example, Amelung, et al [ 50 ] have found that the individual health co-benefits can promote climate-friendly household behavior, and Lee, et al [ 51 ] have also found that factors related to public awareness and risk perception are critical to public participation and support for climate action. More, the findings may help to better understand the relationship between climate change and consumer behavior [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study contributes to consolidate the use of the theory of awe to explain green consumption behavior, showing new results that help to clarify the mediational role of environmental concern and risk aversion to predicting green consumption behavior. For example, Amelung, et al [ 50 ] have found that the individual health co-benefits can promote climate-friendly household behavior, and Lee, et al [ 51 ] have also found that factors related to public awareness and risk perception are critical to public participation and support for climate action. More, the findings may help to better understand the relationship between climate change and consumer behavior [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…When considering the broader findings from both the qualitative results on the "balancing act for sustainable behavior" and quantitative HOPE results about the general preference of households, another explanation for the different effect of health information in the food and the mobility sector seems to fit: The food sector was generally the sector, where people were most willing to change their behavior, while the mobility sector was the one they were least willing to do so [65,66] In the quantitative data no relevant differences in between countries were found [57,65].…”
Section: Discussion Of Health Resultsmentioning
confidence: 90%
“…The QUANTITATIVE part of the HOPE study showed that additional information about direct health co-benefits increased households stated mean willingness to implement climate change mitigation actions in the food and housing sector, but not in the mobility sector [57].…”
Section: Discussion Of Health Resultsmentioning
confidence: 99%
“…In all, there is a uni-directionality in how health is approached. Reducing health impacts is the end-goal while the health benefits that come alongside that reduction, such as improved health and wellbeing related to reduced air pollution or adopting a healthy lifestyle, is not a focus in these agendas [ 38 ]. We argue that the notion of attaining health is a necessary precursor for attaining other goals such as mitigating climate change, protecting biodiversity, and stemming the tide of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%